Analysis of Social, Economic, and Environmental Benefits of the Kuas Jirak Women Empowerment Program as an Implementation of CSR by PT. Pertamina EP Tanjung Field - Afifah, Lina Nur; Andhita, Sabrina Hani (Global Writing Academica Researching and Publishing, 2024)
Kuas Jirak is a community empowerment program organized by PT Pertamina EP Tanjung Field that is specifically dedicated to women in Jirak Village. The Kuas Jirak Program (Jirak Village Women’s Business Group) focuses on empowering women in Jirak Village to enhance human resource capacity and income. This article aims to ascertain the social, economic, and environmental benefits of the Kuas Jirak Program. The research method employed was descriptive research. The study was conducted in July 2024. Sample selection and research location were determined using purposive sampling methods. Primary data were obtained through observations and interviews with the Barokah Group and stakeholders of the Kuas Jirak Program. Secondary data were sourced from activity reports and publications related to the Kuas Jirak Program. The research was conducted in Jirak Village, Pugaan District, Tabalong Regency, South Kalimantan Province. The results of this study indicate that the Kuas Jirak Program has benefits in social, economic, and environmental aspects for the community of Jirak Village, members of the Barokah Group, and the company. Through various empowerment activities carried out by the company, the Social Return on Investment analysis of the Kuas Jirak Program shows a return value of 2.31. Additionally, the Customer Satisfaction Index (CSI) analysis of the Kuas Jirak Program is categorized as very good with a total converted CSI value of 96.25.